2021
DOI: 10.3390/e23060676
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Criticality Analysis of the Lower Ionosphere Prior to the 30 October 2020 Samos (Greece) Earthquake (M6.9), Based on VLF Electromagnetic Propagation Data as Recorded by a New VLF/LF Receiver Installed in Athens (Greece)

Abstract: In this work we present the statistical and criticality analysis of the very low frequency (VLF) sub-ionospheric propagation data recorded by a VLF/LF radio receiver which has recently been established at the University of West Attica in Athens (Greece). We investigate a very recent, strong (M6.9), and shallow earthquake (EQ) that occurred on 30 October 2020, very close to the northern coast of the island of Samos (Greece). We focus on the reception data from two VLF transmitters, located in Turkey and Israel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Our results indicate that criticality was reached for all but one of the examined EQs within a period of 1-2 weeks prior to each one of them, which is consistent with various works studying the LAIC related to the specific EQs [6,30,33,34,36,[57][58][59]. However, in some of the studied EQ cases, non-EQ-related phenomena that could "contaminate" the obtained results indeed existed, so for these cases, the identified criticality could not be definitively attributed to the EQ preparation processes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that criticality was reached for all but one of the examined EQs within a period of 1-2 weeks prior to each one of them, which is consistent with various works studying the LAIC related to the specific EQs [6,30,33,34,36,[57][58][59]. However, in some of the studied EQ cases, non-EQ-related phenomena that could "contaminate" the obtained results indeed existed, so for these cases, the identified criticality could not be definitively attributed to the EQ preparation processes.…”
Section: Discussionsupporting
confidence: 91%
“…The symbols (*), (**), and (***) in the epicenter location indicate an EQ that has been studied in [12,28,29] In the present paper, we investigated the potential energy data associated with these 11 EQs (two of them were considered together due to spatial and temporal vicinity) for possible indications of critical state by means of the so-called natural time (NT) analysis method [10]. NT analysis is a well-established criticality analysis method that has successfully been applied to foreshock seismicity and seismo-electromagnetic signals such as seismic electric signals (SES), ultra-low frequency (ULF) magnetic field variations, MHz fractoelectromagnetic emissions, and VLF sub-ionospheric propagation variations [6,10,[30][31][32][33][34][35][36]. Recently, NT analysis has been used for the thermal channel on surface latent heat flux (SLHF) data, showing criticality indications a few days prior to the 2015 Nepal EQs and the 2016 Kumamoto EQ [37].…”
Section: Introductionmentioning
confidence: 99%
“…VLF changes at separate events are processed by the Shannon entropy. The last one is used as a suitable instrument of searching synergetic processes in the open dynamic system Atmosphere–Ionosphere–Magnetosphere [ 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…In this work, the parameter a was taken as 6, which corresponds with . To improve the detection of periodical oscillations, nighttime data were processed because of their more regular changes [ 38 , 44 ]. During the course of their wavelet transform, the elimination of a polynomial trend was utilized with calculations of the trend by the least-squares method [ 49 ].…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Such studies have revealed that different layers of the model reach critical state before a strong EQ occurrence. Specifically, the criticality analysis method called "natural time" (NT) analysis has successfully been applied to VLF subionospheric propagation data, ULF magnetic field data, global navigation satellite system deformation (GNSS) data, surface latent heat flux (SLHF) data and very recently in stratospheric potential energy ( ), as well to other EQ-related observables such as pre-EQ seismic electric signals (SES), foreshock seismicity, MHz fracto-EM Emissions, also known as fracto-EM Radiation, (FEME/FEMR), [e.g., Politis et al, 2021Politis et al, , 2022Potirakis et al, 2013Potirakis et al, , 2018aPotirakis et al, , 2021Yang et al, 2020;Ghosh et al, 2021;Varotsos et al, 2011, Eftaxias et al, 2018. Additionally, another criticality analysis method called "method of critical fluctuations" (MCF) has been also applied in VLF subionospheric propagation data, MHz FEME/FEMR recordings and ULF magnetic field data [Politis et al, 2021;Potirakis et al, 2016Potirakis et al, , 2018bPotirakis et al, , 2019Contoyiannis et al, 2004a].…”
Section: Introductionmentioning
confidence: 99%